2023
DOI: 10.1038/s41598-023-29473-4
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the acoustic emission and fractal characteristics of coal with varying water contents during uniaxial compression failure

Abstract: To investigate the effect of water on the mechanical properties and acoustic emission (AE) characteristics of coal in the failure and deformation processes. Coal samples of different content were subjected to uniaxial compression tests and AE signals were monitored. The characteristics of the AE signals were further analyzed using fractal analysis. The results show that saturated coal samples have substantially reduced mechanical properties such as uniaxial compressive strength (UCS), dissipation energy, peak … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 61 publications
0
0
0
Order By: Relevance
“…(1) Mechanical characteristic parameter test: The synchronous experimental platform of uniaxial compression and acoustic emission are used, investigating the basic mechanical properties of original and treated coal samples under a normal temperature (30 • C). In the uniaxial compression load, the displacement rate is 0.002 mm/s, the acoustic emission system loads are at an interval of 1 µs, and the sampling frequency is set as 1 MHz [46]. The experimental system will automatically record the relative parameters, such as displacement, stress, and strain, as well as acoustic emission signals during the coal deformation-failure process.…”
Section: Analytical Methods Of Deformation Failure Characteristics In...mentioning
confidence: 99%
“…(1) Mechanical characteristic parameter test: The synchronous experimental platform of uniaxial compression and acoustic emission are used, investigating the basic mechanical properties of original and treated coal samples under a normal temperature (30 • C). In the uniaxial compression load, the displacement rate is 0.002 mm/s, the acoustic emission system loads are at an interval of 1 µs, and the sampling frequency is set as 1 MHz [46]. The experimental system will automatically record the relative parameters, such as displacement, stress, and strain, as well as acoustic emission signals during the coal deformation-failure process.…”
Section: Analytical Methods Of Deformation Failure Characteristics In...mentioning
confidence: 99%
“…Under another external test condition (uniaxial compression strength, acoustic feature and failure form), the results of the uniaxial compression test showed that the attenuation of the uniaxial compressive strength and elastic modulus was very sensitive to increases in the water content [26,27]. In terms of acoustic characteristics, Wu et al [28], Chen et al [29], and Ali et al [30] investigated the stress-strain and acoustic characteristics of coal rocks with different water contents, and determined that the peak AE number and cumulative AE number of coal samples decreased with increasing water content, while the peak AE energy and cumulative AE energy of coal samples both tended to decrease with increasing water content. Gao et al [31] studied the effects of temperature and immersion on the AE and electromagnetic radiation signals of damage under coal and rock loading.…”
Section: Introductionmentioning
confidence: 99%